Orbital and Intracranial Complication Resulting from Acute Rhinosinusitis: Case Report - de Souza, Luana Alves; Verde, Raquel Crisostomo Lima; Lessa, Bruno Farias; de Lima, Clara Mônica Figueiredo; Lessa, Marcus Miranda; Lessa, Helio Andrade (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Among the rhinosinusitis complications, the orbital are the most frequent ones, occurring mostly in the youngsters and children. Simultaneous complications involving the intracranial orbit and space are extremely rare, but they must be severely treated for they have a high rate of morbidity and mortality.Case report: In this work, the authors report a case of a patient who appeared to have preseptal cellulites and epidural abscess, in the form of simultaneous complications of an acute rhinosinusitis. In the patient of this case, choice was made for a clinic treatment associated with a nasosinusal endoscopic surgery and neurosurgical drainage of the intracranial abscess. CT was enough to achieve the diagnosis of this case.Final commentaries: However, it is recommended that, in cases where patients have rhinosinusitis complications, an extensive intracranial investigation needs to be deepened even when this is not so evident in the beginning. Given the polymicrobial nature of these infections, an aggressive culture-guided antibiotic therapy and a multidisciplinary follow-up significantly increase the likelihood of success.
Keywords: orbital cellulites; sinusitis; epidural abscess